Living with oil and coal: Resource politics and militarization in Northeast India - Kikon, Dolly (New Delhi Yoda Press, 2020)
Living with Oil and Coal is full of stories that in their telling and retelling, create and re-create relations among a range of actors, constructing borderlands as sites for citizenship, negotiations over sovereignty, transgressive love, and exchange. Dolly Kikon is a Naga Anthropologist. She is a Senior Lecturer at the School of Social and Political Sciences and teaches Anthropology and Development Studies at the University of Melbourne, Australia.